Racial disparities in gun violence: current evidence, an integrated cascading perspective, knowledge gaps, policy prescriptions - Alex R. Piquero (Frontiers in Public Health, 2026)
At the intersection of public health and violence is the glaring disparity surrounding racial disparities in gun violence. This mini-review summarizes what is known about racial disparities in gun violence, identifies some of the key theoretical frameworks advanced to explain the disparities and located them in an integrated cascading perspective, identifies several research gaps, and concludes by outlining a series of future research issues.